THE DEVELOPMENT OF ARTISTS’ CREATIVITY BASED ON THE METHOD OF “INTUITIVE AESTHETICS”: RESULTS OF EN PLEIN AIRS (LITHUANIA, VILNIUS, 2018) - Balte-Balciuniene, Rasa; Kharitonova, Tatiana; Chekmaryova, Marina (PEOPLE: International Journal of Social Sciences, 2020)
The purpose of this study was to examine the problem of development of creativity of contemporary painters in Lithuania using the Method of “Intuitive Aesthetics”. Development of painter’s personality is one of the most significant problems of contemporary art psychology. Psychologists do a lot of studies, publish articles on the problem of visual communication, impact of the psychological characteristics on art creation, but not enough attention is being paid to the development of methods that would help to develop creativity. Impact of the “Intuitive Aesthetics” method as a way to step out from the stereotypes, that hinder creativity, was researched in the project for Lithuanian painters. 40 well-known Lithuanian painters took part in two En Plein Airs held in Vilnius (Lithuania) in 2018. The “Intuitive Aesthetics” method included four interactions: 1) seminar on art psychology, mindfulness and embodyment; 2) practice for developing skills of reflection; 3) live painting; 4) independent painting. The article presents the results of the research showing how the “Intuitive Aesthetics” method helped to increase the creativity of painters. Method “Intuitive Aesthetics” can be considered as psychological authentication counselling of the painters that help them to step out from the stereotypes that hinder their creativity.